FAKTOR RESIKO ANEMIA PADA REMAJA PUTRI OBESITAS DI BANDAR LAMPUNG TAHUN 2020 - Roza Mulyani; Mindo Lupiana; Andi Eka Yunianto (Poltekkes Kemenkes Mataram, 2021)
Background : Anemia is a problem that often occurs among teenagers, especially young women. Several factors related to adolescent anemia are obesity, calorie intake, protein intake, iron intake, and vitamin C intake. Purpose : The purpose of this study was to analyze risk factors for anemia in obese adolescent girls in Bandar Lampung in 2020. Method : This study used a cross-sectional design. The sample in this study were 100 female students. Data analysis used the Chi-square test to determine the relationship between risk factors and anemia status of adolescent girls. Results : The results of the study were 13% obese adolescent girls, 21% anemia status, 72% very less calorie intake, 49% very less protein intake, 95% very less Fe intake, and 90% very less vitamin C. Faktor yang berhubungan dengan anemia pada remaja putri obesitas yaitu asupan protein (p=0,004) dan lama menstruasi. Factors associated with anemia in obese adolescent girls were protein intake (p = 0.004) and menstrual duration (p = 0.019). Conclusion : Protein intake and duration of menstruation have a significant relationship with the incidence of anemia, but there is no relationship between obesity, calorie intake, intake of Fe and Vitamin C with the incidence of anemia. Researchers suggest that respondents' knowledge is needed in choosing nutritious and balanced foods, nutrition education, especially regarding food selection, and the importance of choosing a nutritionally balanced diet.